Correction: The Complete Sequence of the Acacia ligulata Chloroplast Genome Reveals a Highly Divergent clpP1 Gene - Williams, A.; Boykin, L.; Howell, K.; Nevill, Paul; Small, I. (2015)
The authors would like to amend this article based on the discovery that the originally published Acacia ligulata sequence contains assembly errors, which came to light after the publication of the article.